1993
DOI: 10.1093/nar/21.15.3485
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and properties of oligodeoxynucleotides containing the analogue 2′-deoxy-4′-thiothemidine

Abstract: The 2'-deoxythymidine analogue 2'-deoxy-4'-thiothymidine has been incorporated, using standard methodology, into a series of dodecadeoxynucleotides containing the EcoRV restriction endonuclease recognition site (GATATC). The stability of these oligodeoxynucleotides and their ability to act as substrates for the restriction endonuclease and associated methylase have been compared with a normal unmodified oligodeoxynucleotide. No problems were encountered in the synthesis despite the presence of a potentially ox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
26
0

Year Published

1994
1994
2013
2013

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(27 citation statements)
references
References 28 publications
1
26
0
Order By: Relevance
“…H -S-phosphorothiolate (Vyle et al, 1992;Szczelkun & Connolly, 1995) and a second in which the deoxyriboses at the scissile bonds in both strands are replaced with 4 H -thiodeoxyribose (Hancox et al, 1993;Szczelkun & Connolly, 1995). The equilibrium association constants (K 0 ) in the absence of divalent cation (see the legend to Figure 6) do not differ signi®cantly for the parent 18 bp oligonucleotide (sequence 3, Table 1) and the phosphorothiolate-modi®ed 18-mer; K 0 is only slightly worse (3.1-fold) for the 4 H -thiodeoxyribosemodi®ed 18-mer.…”
Section: The Kinetics Of Complex Dissociationmentioning
confidence: 99%
See 1 more Smart Citation
“…H -S-phosphorothiolate (Vyle et al, 1992;Szczelkun & Connolly, 1995) and a second in which the deoxyriboses at the scissile bonds in both strands are replaced with 4 H -thiodeoxyribose (Hancox et al, 1993;Szczelkun & Connolly, 1995). The equilibrium association constants (K 0 ) in the absence of divalent cation (see the legend to Figure 6) do not differ signi®cantly for the parent 18 bp oligonucleotide (sequence 3, Table 1) and the phosphorothiolate-modi®ed 18-mer; K 0 is only slightly worse (3.1-fold) for the 4 H -thiodeoxyribosemodi®ed 18-mer.…”
Section: The Kinetics Of Complex Dissociationmentioning
confidence: 99%
“…Complementary single strands were annealed, and the products were con®rmed to be >99% in duplex form by non-denaturing gel electrophoresis (16% polyacrylamide, 89 mM Tris-borate, 2 mM EDTA, pH 8.0). Puri®ed oligomers containing a 3 H -S-phosphorothiolate linkage (Cosstick & Vyle, 1989;Vyle et al, 1992) and puri®ed oligomers containing a 4 H -thiothymidine residue (Hancox et al, 1993) were generously supplied by Dr B. A. Connolly.…”
mentioning
confidence: 99%
“…The requirement for precise positioning of the Q loop had been noted previously in studies with a DNA analog where the thymidine adjacent to the scissile bond had been replaced with 4′-thiothymidine, a derivative with sulfur in place of the oxygen in the furanose ring. Oligonucleotides containing this derivative are not cleaved by EcoRV (Hancox et al, 1993), and X-ray crystallography on EcoRV bound to such an oligonucleotide in the presence of MgCl 2 showed that the Mg 2+ ions seen at the active site of wild-type EcoRV were not present with this derivative (D. Kostrewa and F. Winkler, personal communication). However, the Q loop had been displaced as a result of the sulfur atom in the 4′-thiothymidine occupying part of the position for Asn70.…”
mentioning
confidence: 99%
“…Studies with chemically synthesized oligonucleotides containing 4'-thlo-z -deoxynucleotides have shown (Hancox et al, 1993;Boggon et al, 1996; GD. Jones and RT Walker, unpublished results), that 4'-thiothymidine destabilizes a DNA helix very slightly and TEDU causes substantial destabilization.…”
Section: Discussionmentioning
confidence: 99%